2012
DOI: 10.1136/bmj.e6077
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of single progesterone test to predict early pregnancy outcome in women with pain or bleeding: meta-analysis of cohort studies

Abstract: Objective To determine the accuracy with which a single progesterone measurement in early pregnancy discriminates between viable and non-viable pregnancy.Design Systematic review and meta-analysis of diagnostic accuracy studies.Data sources Medline, Embase, CINAHL, Web of Science, ProQuest, Conference Proceedings Citation Index, and the Cochrane Library from inception until April 2012, plus reference lists of relevant studies.Study selection Studies were selected on the basis of participants (women with sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 34 publications
3
67
0
6
Order By: Relevance
“…[18] Verhaegen J et al (2012) also concluded that a single progesterone measurement for women in early pregnancy presenting with bleeding or pain and inconclusive ultrasound assessments can rule out a viable pregnancy. [19] In a study done by Abdelazim IA et al(2013), the mean serum progesterone of the studied population was significantly higher in the viable pregnancy group (46.5±7.4 ng/mL) compared to non-viable pregnancy group (9.9±4.8 ng/mL; p<0.05). [20] In my study, progesterone supplements (Oral micronized progesterone twice daily) were given to all the cases, irrespective of their serum progesterone levels, as per the institute protocol, however nothing could be proven as regards to decreased rate of abortions.…”
Section: Discussionmentioning
confidence: 89%
“…[18] Verhaegen J et al (2012) also concluded that a single progesterone measurement for women in early pregnancy presenting with bleeding or pain and inconclusive ultrasound assessments can rule out a viable pregnancy. [19] In a study done by Abdelazim IA et al(2013), the mean serum progesterone of the studied population was significantly higher in the viable pregnancy group (46.5±7.4 ng/mL) compared to non-viable pregnancy group (9.9±4.8 ng/mL; p<0.05). [20] In my study, progesterone supplements (Oral micronized progesterone twice daily) were given to all the cases, irrespective of their serum progesterone levels, as per the institute protocol, however nothing could be proven as regards to decreased rate of abortions.…”
Section: Discussionmentioning
confidence: 89%
“…It is advisable to combine it with the other tests [9]. Current meta-analysis supported the paradigm shift toward benefit of serum progesterone level alone [7]. Al Jufairy also reported that lower level of progesterone could predict not only miscarriage but also ectopic pregnancy [10].…”
Section: Discussionmentioning
confidence: 98%
“…Also, we had limited data regarding other potentials confounders being reported elsewhere (e.g. chromosomal abnormality, quantitative data about maternal complaints of bleeding and pain, paternal age, and maternal consumption of potential related compounds) [7,14,21,22]. However, our study performed in outpatient setting where most of Indonesian women seek medical advice for their pregnancy for the first time based on author's knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations